How deal the grade work? A problem or an opportunity to complete the development of skills - Rekalde Rodríguez, Itziar (Revista Complutense de Educación, 2012)
In this moment the University has a great challenge; design, develop and evaluate Final Grade Work, and this paper aims to give clarity about this issue. In order to introduce the reader into this topic, we show the information found on the net about this topic in 27 degrees of 22 Spanish universities, and 5 normatives. Then, we present a proposal for action which includes guidelines to work from a videographic look (like a process) and another photographic (like a product) the Final Grade Work.